Comparison of playing pattern and d penetration area between winning team and losing team in rabobank fih hockey world cup 2014 tournament / Shahrul Redza Zahid - Zahid, Shahrul Redza (2015)
The purpose of this study was to make Comparison between Winning and Losing in their Playing Pattern and the D Penetration Area in Rabobank FIH Hockey World Cup 2014 Tournament. The Eight games from qualification match of field hockey were analyzed from Rabobank FIH Hockey World Cup 2014 Tournament. The variables studied were: win or lose game result, variables related to D penetration, and variables related to pattern of play. The inter-observer correlation of 0.0 represents no association between the values, whereas a correlation of 1.0 which values of 0.7 indicate a moderate correlation, 0.8 good and 0.9 denotes a very good association. This study found no significant differences between winning and losing teams in the following variables: D penetration zone (left, middle and right), Pattern of shot field goal (combination passes to goal, left, middle and right upper goal post, also left, middle and lower right goal post, Score, miss and save).All of the data that have been gathered showed based on descriptive and nonparametric statistic, Wilcoxon signed-ranks test where the statistical value is set at p≤0.05. From the results, it can be concluded that all of the team would have equal chances to be a winner. Both of the winning and losing team can be the winner. But, in the international level matches for men's hockey at the highest level are often very even, because each of the team are very equal in the skills acquisition, tactics and patterns of play, and physical abilities from each player. Comparison research on the team ability of males and females players need to be conducted in further research.